Reduced mobility but high survival: thermal tolerance and locomotor response of the specialist herbivore, Pareuchaetes insulata (Walker) (Lepidoptera: Erebidae), to low temperatures. Issue 4 (15th December 2016) - Uyi, O.O.; Zachariades, C.; Marais, E.; Hill, M.P.
Abstract: Disentangling the responses of insects to variations in their thermal environment is central to our understanding of the evolution of temperature-dependent performance in these species. Here, we report results of experiments examining the effects of high (upper lethal temperature = ULT) and low (lower lethal temperature = LLT) temperature and exposure time on the survival of larvae and adults of a multivoltine, nocturnal moth species, Pareuchaetes insulata, a biological control agent whose impact on an invasive weed, Chromolaena odorata has been variable in South Africa. The influence of temperature and acclimation on locomotion performance of the moth was also investigated. Temperature and duration of exposure significantly affected survival of both adults and larvae of P. insulata with more extreme temperatures and/or longer durations proving to be more lethal. Third instar larvae and adults are both freeze intolerant and had LT50 of −5.9 and −4.7°C, respectively, after a 2 h exposure. Although cold acclimation was beneficial to the nocturnal larvae, temperatures below 10°C significantly reduce their locomotion activities. The average daily minimum temperatures in the coldest months at three locations in South Africa are over 5°C lower than those of Fort Lauderdale, Florida, USA, where P. insulata was originally collected. Our results suggest that lethal high or low temperatures at short timescales are trivial in explaining the variable performance of P. insulata, but reduced locomotion at sub-lethal temperatures may be an important driver of the population dynamics of the biocontrol agent (especially in winter months) and may consequently explain the low population levels of the moth because of possible reduced feeding by larvae during night-time low temperatures.